(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
The study attempts to develop a new taxonomy in the field of e-Learning. Redefining the pursuit of digital education, contact-offline; a contact online form; focuses on the concepts of the flipped classroom; covers distance learning, distance learning, interprets issues of virtual learning, distance learning, hybrid and blended form. He argues that there is an urgent need to develop a new kind of typology, redefining existing concepts, rethinking forms of distance education, changing perspectives: approaching the topic from the direction of e-Learning. Compared to previous formulations, in the present study we consider various traditional and technology-supported learning modes as possible learning organization procedures. The “turning point” does not appear in the field of technology involvement and not in the field of presence-absence learning, but in the field of learning organization.